Toxins and Contaminants in Indian Food Products - Sharma, Ramesh Kumar; Parisi, Salvatore (Springer International Publishing : Imprint: Springer, 2017)
This book discusses different aspects of contamination in Indian food products. Particular attention is given to the presence and analytical detection of detrimental substances such as pesticides, mycotoxins and other biologically-produced toxins, food chemicals and additives with natural or industrial origin. Furthermore, the book addresses the production and the commercial exploitation of native botanical ingredients, and the question if such ingredients should be regarded as foods or drugs. It also sheds light on chemical aspects of organic farming practices in India. Readers will also find information on pesticides and other detrimental chemicals detection in Indian farming. The authors present a useful opinion on how and why food contaminants can lead to border rejections during export, in particular to the European Union.< .